Natural and synthetic cosmetics: An evaluation from an Islamic perspective and health implications for Muslim consumers - Nur Ilma Ambo; Musaiyadah Ahmadun; Masnih Mustapa; Nur Faizatul Zehan Saari; Syamsul Azizul Marinsah; Zalina Zakaria (Global Academic Excellence (M) Sdn Bhd (GAE), 2025)
This study explores the comparison between natural and synthetic cosmetics from an Islamic perspective, focusing on their implications for Muslim consumers' health and well-being. With the growing demand for halal-certified and safe beauty products, the research investigates how natural cosmetics align with the concept of Halalan Tayyib an—which emphasizes purity, safety, and ethical considerations in Islamic teachings. The study also examines the potential health risks associated with synthetic cosmetics, which often contain harmful chemicals such as parabens, mercury, and silicones. These substances pose long-term health threats and raise concerns regarding their halal status. The paper further highlights the challenges and opportunities for the cosmetics industry in ensuring compliance with Islamic principles, particularly in sourcing, production processes, and packaging. Through a qualitative approach and a review of literature, the study provides insights into how Islamic values influence consumer behavior in the cosmetic market and suggests ways to foster greater awareness among Muslim consumers. The findings emphasize the need for a more comprehensive halal certification system and stricter regulation of cosmetic products to safeguard both religious integrity and public health. The research contributes to the growing discourse on halal cosmetics and their role in promoting the holistic well-being of Muslim consumers.